The impact of aid on total government expenditures: New evidence on fungibility - Łukasz Marć (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Aid is said to be fungible at the aggregate level if it raises government expenditures by less than the total amount. This happens when the recipient government decreases domestic revenue, decreases net borrowing, or when aid bypasses the budget. This study makes three contributions to both fungibility and fiscal response literature. First, fungibility at the aggregate level is re-examined on a bigger recent panel dataset, distinguishing between short- and longterm impact of aid. The results indicate that aid is partly fungible in the long run and highly fungible in the short run. Second, to account for aid bypassing the budget, technical cooperation is used as a proxy for off-budget aid. Off-budget aid is found to be non-fungible and on-budget aid is partly fungible. Third, fungibility of bilateral and multilateral aid is analysed: the results indicate lower fungibility of multilateral aid.
Keywords: E62; F35; H50; O23; 330; foreign aid; fungibility; fiscal response; government expenditures